Deposition of dry particles on a fin-and-tube heat exchanger by a coupled soft-sphere DEM and CFD. (March 2020) - Välikangas, Turo; Hærvig, Jakob; Kuuluvainen, Heino; Dal Maso, Miikka; Peltonen, Petteri; Vuorinen, Ville
Highlights: Novel method for the selection of adhesion properties was demonstrated for dry particle fouling. The method enables the comparison of the volume fouling rate of the fin-and-tube heat exchanger fin shapes. The volume fouling rate was 1.76 to 5.4 times higher with ReDh = 793 than at ReDh = 264. High adhesive particles have 3.0 times higher volume fouling rate than low adhesive particles for both fin shapes and particle sizes. Herringbone fins have 1.74 and 1.8 times higher volume fouling rate than plain fin shape for low and high adhesive type particles. Abstract: In this study, a novel computational model is utilized for investigating fouling of two commonly encountered heat exchanger fin shapes in an air-conditioning application. The computational method utilizes the discrete element method (DEM) coupled with a large-eddy simulation (LES) framework. The fin-and-tube heat exchangers (FTHE) are investigated for three different Reynolds numbers ( R e D h = 243, 528, 793), three different particle sizes ( D p = 5, 10, 20 µm) and two different adhesive particle types based on the experimental values in the literature. The code is first benchmarked from the CFD and DEM viewpoints. A comprehensive fouling study of the FTHE's, consisting of altogether 36 simulations, is then carried out. The major numerical findings of the paper consist of the following four features. First, with low adhesive particles, the plain fin shape has a 3.45 higher volume fouling rate with R e D h = 793 than at R e D h = 264. With the herringbone fin shape, and the low adhesive particles, the volume fouling rate is 1.76 higher with R e D h = 793 than at R e D h = 264. Second, for the high adhesive particles, the plain fin has a 5.4 times higher volume fouling rate at R e D h = 793 than for R e D h = 264. The herringbone fin shape has a 3.92 times higher volume fouling rate with the highest Reynolds number of R e D h = 793 compared to R e D h = 264. Third, high adhesive particles have 3.0 times higher volume fouling rate than low adhesive particles for both fin shapes, all particle sizes and all Reynolds numbers combined. And finally, herringbone fins have 1.74 times higher volume fouling rate than plain fins for low adhesive particles. For high adhesive particles, herringbone has 1.8 times higher volume fouling rate and when both particle types are summed together, herringbone has a 1.78 times higher volume fouling rate than the plain fin shape. As a major finding of the study, the high adhesive particle collection efficiency increases monotonously with the Stokes and Reynolds numbers while low adhesive particle collection efficiency poses a non-monotonous trend.